Exploitation of Children’s Criminal and Economics To Become A Drug Course In The Urban Of Makassar Indonesia - Ramlan, Herdianty; Kasnawi, Tahir; Manda, Darman; Kamaruddin, Syamsu; Syukur, Muhammad (KnE Social Sciences, 2024)
Many studies have examined the sexual exploitation of children few have explored the economic and criminal exploitation, mostly using qualitative research. In addition, not many studies have been done on children who are economically exploited by their own parents who force them to work as drug couriers. This study used a mixed methods concurrent embedded model to obtain more comprehensive data with 15 child victims of exploitation and 150 respondents as informants. Data collection, data analysis, and data validity were done using qualitative and quantitative methods. The results showed that drug couriers were a form of economic exploitation as well as criminal exploitation of children by families. The contributing factor is the child’s fear of parents who always commit violence, although children worked as drug couriers because of their own desire to help the family economy and personal needs. The social environment contributes to the exploitation of children because it is in the social environment of children that helps parents work, thus undermining parents’ care for their children. Various methods are used if the child does not want to work as a drug courier, such as physical violence, psychological violence and threats, and sometimes giving gifts and freedom of association. The actions of parents are economic exploitation and crime against children. Keywords: exploitation, drug couriers, economic, family